Tinjauan Hukum Islam Terhadap Praktik Jual Beli Air Susu Ibu (ASI) di Sekretariat Aimi Kecamatan Ujung Pandang Kota Makassar Sulawesi Selatan - Aprilia Sri Muthmainnah; Siti Ramlah Usman; Yossie M. Y. Jacob (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of writing This For understand the review of Islamic law regarding the practice of buying and selling breast milk (ASI) in Ujung Pandang District, Makassar City. The theoretical benefit of this research is that it is hoped that this research can provide a useful contribution to the development of knowledge regarding the buying and selling of breast milk in society and the attitude of the government and religious figures towards the practice of buying and selling breast milk (ASI) in handling it and practically, it is hoped that this research can help provide ideas for the community and readers regarding the buying and selling of breast milk from the perspective of Islamic law. The research method is empirical juridical research. The results of this research show (1) An overview of Islamic law regarding the practice of buying and selling breast milk (ASI) in Makassar City, especially in Ujung Pandang District, namely that it should not allow buying and selling breast milk (ASI), because there are many disadvantages (damage/danger). Because the buying and selling of breast milk (ASI) which is carried out through the Indonesian Association of Breastfeeding Mothers (AIMI) does not have recorded data so the source of breast milk (ASI) is not clear between the sellers and buyers of breast milk (ASI). (2) Factors that influence the practice of buying and selling breast milk are as follows: 1. Economic factors, where the perpetrators of buying and selling breast milk (ASI) are breastfeeding mothers who are still young and some of them are not able to produce breast milk. (ASI) is good, where the perpetrators of buying and selling breast milk (ASI), especially respondents who sell breast milk (ASI), experience financial shortages, so they choose to sell breast milk (ASI) through the Indonesian Breastfeeding Mothers Association (AIMI). 2 the religious factor, which is due to a lack of education and support from the family so that many perpetrators of buying and selling breast milk (ASI) do not really understand the importance of religious knowledge in carrying out the practice of buying and selling breast milk (ASI). Conclusions of Writer are: (1) Overview Islamic law regarding practice sell buy breast milk (ASI) in Makassar City, especially in Ujung Pandang District , namely should No allow exists sell buy breast milk (ASI), because Lots harm ( damage / danger ). Suggestions from Writer are: (1) It is better not to breastfeed (ASI). bought and sold in a way illegal nor free. (2) Necessary exists supervision morestrict from institution government nor non- governmental institutions local about practice sell buy breast milk (ASI) so you don't happen.